O que restou é Folclore: o negro na historiografia alagoana - Silva, Jeferson Santos da (2014)
The reference to the past when the Alagoa s old elites talks about black people is a fact for anyone interested in black people history in such place. Although such reference be present at the most of publications that discussed on blacks, it will be in the folklore studies that such prospective will find it place. Despite of evolution on black studies and it s culture it going from your complete depreciation to your acknowledge and valorization , what we had in fact didn t represent a significant change in the elite s broach about that issue. Such way of broach represented the final stab on the black people existence on that region (north-east), because, if is true that black people is not inferior anymore, it s also true that blacks are not between us, because they are part of our past now